STUDI KOMPARASI HASIL BELAJAR BIOLOGI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF ANTARA TIPE STAD DAN TGT BERDASARKAN KARAKERISTIK PESERTA DIDIK DI SMA NEGERI 1 SENTANI - Andaningsih, Wresni; Wilujeng, Sri (Jurnal Ilmu Pendidikan Indonesia, 2015)
This research aims is to know difference between real students learning of metabolism by using STAD type learning and TGT type learning model based on interest and character of students learning. To achieve this aim it will be implied STAD type learning model and TGT type learning model based on interest and character of student learning to student of SMA Negeri 1 Sentani, grade XI IPA (Science) consists of one hundred students are as objects of research. They are result metabolisme learning compared by using both STAD type and TGT type based on interest and character o students learning. This data result is metabolisme learning to be collected by using achievement test. While is about interest and being active of students learning gotten from interest questionnaire of using both STAD type and TGT type and students learning observation the the research data collection is analyzed by using Independent sample test and Technique Correlation Product Moment Person. This research shows: 1). Implementation of TGT type Learning model more objective to show the result of learning process than by using STAD type learning model. It is implied in both active class and inactive class. Based on the result of the analysis of value average TGT learning in the first test on active class X Ì TGT = 76,04 > X Ì STAD = 59,19. So did second test X Ì TGT = 79,87 > X Ì STAD = 66,50. As well as for the inactive class value average on the first test X Ì TGT = 71,19 > X Ì STAD = 54,25 and also the second test X Ì TGT = 72,33 > X Ì STAD = 63,93. 2). There is no correlation between learning interest with leaning result of student in both active class and inactive class. 3). There is no correlation between students learning being active with learning result in both active class and inactive class. Key words: STAD, TGT, Learning Result, Biology, Characteristic